Politicians on the Board of Directors: Do Connections Affect the Bottom Line? - Hillman, Amy J. (Journal of Management, 2005)
Resource dependence theory emphasizes the importance of linking firms with external contingencies that create uncertainty and interdependence. A critical source of external interdependency and uncertainty for business is government. One way to link a firm to the government is appointing ex-politicians to the board of directors. This study compares the boards of two groups of firms—those from heavily and less regulated industries—and finds the former group has more politician directors. Firms with politicians on the board are associated with better market-based performance across both groups, although the relationship is more pronounced within heavily regulated industries.